A High-Resolution 14C Chronology Tracks Pulses of Aggradation of Glaciofluvial Sediment on the Cormor Megafan between 45 and 20 ka BP. Issue 3 (22nd March 2018) - Hippe, Kristina; Fontana, Alessandro; Hajdas, Irka; Ivy-Ochs, Susan
Abstract: During the Last Glacial Maximum (LGM) the Tagliamento glacier delivered large amounts of sediment to the Cormor alluvial megafan on the southern Alpine foreland basin. To build a chronology of Late Pleistocene glacier fluctuations and assess the timing of the transition from interstadial to glacial conditions, we have performed radiocarbon ( 14 C) dating on peat and macrofossil samples obtained from a drilling core from the distal Cormor megafan. Our chronology records fluvial and glaciofluvial aggradation from the end of MIS 3 until the end of the LGM. It shows a rapid transmission of signals of environmental change along the Cormor megafan, so that changes in the activity of the Tagliamento glacier directly affect glaciofluvial sedimentation. Our data demonstrate that the intrinsic heterogeneity of peat is most critical for the reliability and reproducibility of the obtained 14 C ages. Macrofossil subsamples give evidence for significant mixing of organic components of different ages within single peat samples. Sample heterogeneity is also underlined by the results obtained from testing of different laboratory precleaning methods. Our results suggest that a rigorous ABA pretreatment is sufficient for peat cleaning. In contrast, the chemically stronger ABOX methods appear to rapidly degrade the peat, particularly destroying older organic components.